Strategi Pemanfaatan Media Sosial dalam Pengembangan Dakwah Majelis Ta'lim Darul Futuh Kabupaten Bogor - Muhammad Fadlurrohman Mauludi; Hasan Basri Tanjung; Santi Lisnawati (Da'watuna: Journal of Communication and Islamic Broadcasting, 2022)
The development of Islamic da'wah activities is quite significant in terms of the number of followers, materials, methods, and media used. Advances in current technological flows make social media can function as a medium of da'wah both individually and institutionally. This study aims to describe the strategy of using social media in the development of da'wah in the Darul Futuh Ta’lim Assembly, Bogor Regency. The research method used is descriptive qualitative with a field study approach. The data collection technique using the methods of observation, interviews, and documentation. The procedure of data analysis was carried out by descriptive analysis method. The results showed that several social media such as Youtube, Facebook, Instagram, and Websites were used as a means of preaching. The strategy is carried out through the stages of formulation, implementation, and evaluation. The stages of the strategy include determining the social media used, recognizing the characteristics of social media, the target of da’wah on social media, the topic of the da’wah material being delivered, creating content, utilizing the availability of social media features, and disturbing or uploading content so as to get feedback from various parties. Keywords: Strategy, Social Media, Da'wah, Ta'lim Assembly.